Polymorphism of vascular endhothelial growth factor (VEGF) gene insertion/ deletion -2549 as risk factor of diabetic retinophathy in Javanese patients with type 2 diabetes - Maliyah Madiyan, Jems Kifen Roget Maay Ahmad Hamim Sadewa (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2012)
Diabetic retinopathy (DR) is a visual disorder caused by the diabetic microvascular complications.Genetic polymorphism in the vascular endothelial growth factor (VEGF) gene plays an importanrole in the susceptibility of DR. The aim of this study was to evaluate the association of thepolymorphism of VEGF gene insetion/deletion (I/D) -2549 with DR in Javanese type 2 diabetesmellitus (DM) patients. This was a case control study involving 40 Javanese type 2 DM patientswith DR as case subjects and 40 Javanese type 2 DM patients without DR as control subjects.Type 2 DM patients with DR were recruited from Eye Polyclinic, whereas type 2 DM patientswithout DR were recruited from Endocrine Polyclinic of Dr. Sardjito General Hospital, Yogyakarta.Genotyping of VEGF gene I/D-2549 was conducted using PCR-RFLP method. Plasma VEGFlevels were measured using Enzym-Linked Immunosorbent Assay (ELISA). The genotype distributionof DD (67.5%) and the allele frequency of D (82.5%) in type 2 DM patients with DR was higherthan those without DR (27.5% for DD genotype and 56.3% for D allele). The OR of DD and IDgenotypes versus II genotype between type 2 DM patients with DR and without DR was 6.882(95%CI: 0.789-60.060; p=0.048), whereas OR for the D allele versus I allele between type 2 DMpatients with DR and without DR was 3.667 (95%CI: 1.773-3.667; p=0.000). The plasma VEGFlevels of DD genotype (92.16Â±49.73 pg/mL) were significantly higher than ID genotype(42.70Â±33.29 pg/mL) in type 2 DM patients (p=0.000). In conclusion, the polymorphism ofVEGF gene I/D -2549 is associated with DR in Javanese type 2 DM patients. The DD genotypeand D allele of the VEGF gene polymorphism are the risk factor of DR in those patients. Theassociation of the polymorphism of VEGF gene with DR may be explained with the high plasmaVEGF level.Keywords: vascular endothelial growth factor (VEGF) - polymorphism - diabetes - retinopathy- Javanese patients